Faktor-Faktor Pengaruh Perilaku Pembelian Konsumen dalam Model Online to Offline pada Merek Uniqlo di China - Que Jiaming; Fitroh Adhilla; Sukardi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to explore and analyze the influence of corporate image, service product image, user image, and store physical conditions on consumer purchasing behavior in the online-to-offline (O2O) model for the Uniqlo brand in China. Utilizing an associative quantitative approach, primary data was collected through an online questionnaire distributed to 375 respondents who are Uniqlo consumers, using purposive sampling methods. Data analysis was performed using multiple linear regression. The results indicate that corporate image, service product image, and user image have a significant and positive impact on consumer purchasing behavior, while store physical conditions do not show a significant effect. These findings emphasize the importance of building a positive image and providing quality service to enhance consumer purchasing decisions within the O2O context.